Produção, caracterização e aplicação de biossurfactantes de Candida lipolytica e C. glabrata utilizando resíduos industriais como substratos alternativos - Andrade, Rosileide Fontenele da Silva (2010)
The biosurfactants are amphipathic compounds produced by microorganisms with several important environmental and industrial applications, whose metabolites has been investigated, mainly by the advantages of biodegradability, production from renewable resources and functionality under extreme conditions. However, its use depends on the cost of production and purification, and compared to synthetic surfactants. Thus, in this work the use of resources consisting of industrial waste (Manipueira, corn steep liquor and whey) as low-cost alternative in the production of biosurfactants by the strains of the genus Candida. The studies were carried out initially with the strain of Candida lipolytica, maintained in the cultures of the Center for Research in Environmental Science UNICAP, to establish the formulation of a new medium for biosurfactant production using cassava wastewater as substrate according to factorial design 23. The results showed a reduction in surface tension of water 72mN / m to 26.35 mN / m by the biosurfactant produced by Candida lipolytica in medium formulated with 10% of Manipueira, 0.2% of ammonium sulfate and 0.1% of urea after 96 hours of culture. The biosurfactant produced was characterized as polymer composition due to high in carbohydrates, proteins and lipids, and shows high stability in a wide range of temperatures, showing efficiency in bioremediation processes by removing 81.7% of burnt motor oil is present in soil. The investigations were continued by a wild strain of Candida glabrata, isolated from soil in semi-arid, PE, Brazil. The isolated yeast was identified by morphology, by biochemical and molecular as C. glabrata, demonstrating the potential of producing biosurfactant using an experimental design type DCCR (central composite rotational design), using industrial waste corn steep liquor and whey, with significant reduction in surface tension of water from 72 to 28.53mN / m The isolated biosurfactant produced by C. glabrata, was described as due to high polymeric composition of lipids, proteins and carbohydrates demonstrating stable in high concentrations of sodium chloride, and remove 95% of burned motor oil in sandy soil. Because of the potential reduction of surface tension by C. lipolytica and C. glabrata, the process of production of these biosurfactants become economically viable due to the use of industrial waste to obtain these biopolymers, making the economic process with great potential for application in environmental processes